Побудова точок спостереження при класифікації текстів машинним навчання поліноміальних моделей - Голуб, Марія (Видавництво Львівської політехніки, 2018)
To expand the capabilities of multilevel monitoring technology, a new method for converting text into a typical input data array is proposed. Unlike existing ones, the variance is used to form observation points. The growth of the number fo well-classified texts has been experimentally confirmed.
Keywords: класифікація текстів; машинне навчання; МГУА